Sistem Pakar Untuk Mendiagnosa Penyakit Dalam Dan Menentukan Jenis Tanaman Herbal Serta Cara Pengolahannya Dengan Menggunakan Metode Certainty Factor (CF) - Arif, Muhammad; Al Islami, Hidayatullah (CV. Shofanah Media Berkah, 2024)
Internal medicine is a disease that usually attacks humans. Most of the internal diseases that occur are often considered trivial, and if the disease is not treated immediately it will become more serious and serious. So because of that we need a tool or system that has the ability like a doctor in diagnosing this internal disease. The system is an expert system that solves problems as is usually done by experts. This study aims to create an expert system application for diagnosing internal medicine. The application of this system diagnoses internal medicine with the Prototype and the Certainty Factor method. The Certainty Factor method is a method for proving whether a fact is certain or uncertain. This method provides space for experts to give confidence in the knowledge they express. From calculations using the Centainty factor method for each disease, from the symptoms entered by the user for hypotension the probability is 0.92% or 92%, while the symptoms entered by the user for hypertension are likely to be 0.994624 or 99.46%, from the results of the comparison the probability is obtained the maximum value of CF is 0.994624 or 99.46% with hypertension.